The essence of the surrogacy contract and its legal features (Journal of actual problems of jurisprudence, 2022)
The article examines the definition of the surrogacy contract, its essential and other conditions; disclosing the content of the subjective rights and legal obligations of the surrogate mother and spouses (customers); as well as substantiating the relevance of regulating relations between the surrogate mother and spouses (customers) on a contractual basis, as well as establishing the impact of this method of regulating these relations on the procedure for determining the origin of a child born as a result of the use of reproductive technologies.With the development of science and innovative technologies, new problems arise, one of which is the problem of surrogacy. The foundations of legal regulation of surrogacy in Kazakhstan originate in 1998 with the adoption of the Law "On Marriage and Family", which provided for the right to use this method as assisted reproductive technologies (ART). In 2004, the Law of the Republic of Kazakhstan "On reproductive rights of citizens and guarantees of their implementation" was adopted. In 2009, the Code of the Republic of Kazakhstan "On the Health of the People and the healthcare system" was adopted, which provides for the basics of legal regulation of surrogacy. On December 26, 2011, the Code of the Republic of Kazakhstan "On Marriage (Matrimony) and Family" was adopted, in which Chapter 9 contains a section "Surrogacy and the use of assisted reproductive methods and technologies".Keywords: surrogate mother, family law, child, spouses.